PDTM-28. THE CONTRIBUTION OF PAX GENES AS NOVEL TUMOR SUPPRESSORS IN GROUP 3 MEDULLOBLASTOMA. (5th November 2018) - Zagozewski, Jamie; Morrison, Ludivine; Stromecki, Margaret; Palidwor, Gareth; Ramaswamy, Vijay; Werbowetski-Ogilvie, Tamra
Abstract: Medulloblastoma (MB) is the most common malignant primary pediatric brain tumor. Of the four distinct molecular MB subgroups, Group 3 MB has the worst prognosis, is highly metastatic, and is poorly defined with regard to the pathways that contribute to tumor progression. OTX2 is overexpressed/amplified in 80% of Group 3 MB, where it contributes to increased self-renewal and reduced neuronal differentiation. In order to identify genes associated with an OTX2 gene regulatory network in Group 3 MB cells, we mapped changes in active (H3K4me3) and repressive (H3K27me3) histone modifications following OTX2 silencing in Group 3 MB tumorspheres by ChIP-sequencing. Genes with significant changes in H3K27me3 profiles were associated with neuronal differentiation while genes that had significant changes in H3K4me3 profiles were associated with cell cycle progression. Interestingly, significant loss of H3K27me3 was observed for 114 transcription factors, indicating an overall de-repression of transcription factor expression following OTX2 silencing. Members of the PAX gene family were among the transcription factors de-repressed upon OTX2 silencing, and their role in MB progression has not been explored. Expression analysis in a cohort of 763 patient samples demonstrated that PAX3 and PAX6 expression is significantly lower in Group 3 MB. Reduced expression of PAX3 and PAX6 in Group 3 MB correlated with a significant reduction in overall patient survival. Following OTX2 knockdown in established and newly derived Group 3 MB cell lines, significant increases in PAX3 and PAX6 expression were observed providing further support for our ChIP-sequencing data. Finally, silencing of PAX6 expression resulted in an increase in cell growth suggesting a putative tumor suppressor role in Group 3 MB. Our ongoing and future studies include the further evaluation of putative divergent regulatory roles of OTX2 and PAX6 controlling neuronal differentiation in Group 3 MB.